Socio-ecological innovations in marketing strategy – a comparative analysis of companies operating in Western European countries and Central-Eastern European countries - Rudawska, Edyta; Frąckiewicz, Ewa; Wiścicka-Fernando, Małgorzata (Economics and Business Review, 2018)
The aim of the paper is to assess the attitudes of company managers in the food and drink sector in Western Europe and Central-Eastern Europe towards implementing marketing strategies that take into account not only economic, but social and ecological aspects as well. Innovation is a growing topic among scholars when discussing issues related to the enhancement of company performance and competitiveness.Such innovation may refer to technological changes (new products, processes), as well as non-technological ones referring to various marketing and organizational methods. In the paper the authors focus on innovations in marketing activities arising from the application of a more socio-ecological orientation. The paper comprises two parts: one theoretical, one empirical. In the first part the role of innovation in the process of creating company competitiveness is presented, as well as the concept of an innovative marketing strategy. In the second part the results of international research are discussed.